2018
DOI: 10.15171/apb.2018.028
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Synthesis of Silver Nanoparticles by Two Techniques Using Saturaja rechengri Jamzad Extract: Identifying and Comparing in Vitro Anti-Proliferative Activities

Abstract: Purpose: A lot of plants are available which can produce nanoparticles used in medicine, life sciences, and the pharmaceutical industry. The present study aims to introduce safe biological and eco-friendly methods for synthesizing silver nanoparticles (AgNPs) by using Saturaja rechengri Jamzad extract, which can replace traditional chemical methods. In addition, the chemical nature and antimicrobial activities were identified and accordingly the anticancer effects of AgNPs was successfully reported on colon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Similar to the findings of this study (Table 3), a new finding indicated that S. aureus was more sensitive to chitosan/PVA nanocomposite than E. coli (Hajji et al, 2016). Dislike, The S-AgNP/Pho extract showed greater effect on the both bacteria (same effectiveness) compared to S-AgNP/Ult one (Narchin et al, 2018). The afore-mentioned differences of the efficiency on the both bacteria may be due to a few factors such as size of AgNPs, types of nano-metals (Meral et al, 2019), bacterial resistance, growth phase of herbs, major composition of extract, and the experiment methodology (Alizadeh, 2015;Paredes et al, 2014).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to the findings of this study (Table 3), a new finding indicated that S. aureus was more sensitive to chitosan/PVA nanocomposite than E. coli (Hajji et al, 2016). Dislike, The S-AgNP/Pho extract showed greater effect on the both bacteria (same effectiveness) compared to S-AgNP/Ult one (Narchin et al, 2018). The afore-mentioned differences of the efficiency on the both bacteria may be due to a few factors such as size of AgNPs, types of nano-metals (Meral et al, 2019), bacterial resistance, growth phase of herbs, major composition of extract, and the experiment methodology (Alizadeh, 2015;Paredes et al, 2014).…”
Section: Resultssupporting
confidence: 88%
“…The psychrophiles grew fast at 4 °C and no growth was observed at 8 °C after 3rd day of cold preservation, irrespective of the types of coating and sampling days. On the other hands, S-Aqueous/PVA showed the wave, indicating smaller nanoparticles in the aqueous solution (Narchin et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this research were compared with previous researches on Satureja family plants. The results showed a potential anticancer effect of Summer Savory compared to other plants [56,57]. Many efforts have been made to identify the mechanism of the effect of AgNPs on different cancer cell lines.…”
Section: Cytotoxic Effect Of Ag Npsmentioning
confidence: 94%
“…However, materials such as sodium borohydride and cetyl trimethylammonium bromide (CTAB) intensify the toxicity of the environment, and this matter raises concern among researchers, especially in biomedical applications. Hence, many prior research considered bio-friendly reagents as an alternative to replace toxic reducing agents in the synthesis of nanoparticles, such as phytochemicals [ 11 , 12 , 13 ]. Phytochemicals are naturally extracted compounds found in plants that can be classified into several groups, such as natural gum, that act as a stabilizer.…”
Section: Development Of Nanofluids Using Green Technologymentioning
confidence: 99%